Kemajuan Budaya Masyarakat Makassar Abad XVII - Susmihara Susmihara (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2016)
The plurality of social life of Makassar society in XVII century is a central point in the realization of gaining progress and performance in Makassar at the time. The plural life marked by principle of